The Existence of the Tondano Javanese Muslim Community in Maintaining Harmony - Rohmatul Faizah; Fauzul Aliwarman (Future Science, 2020)
Indonesia is a country that has many ethnicities and ethnic groups, and therefore Indonesia is also a multi-cultural and very pluralistic country. This makes Indonesia a country that is rich in culture but on the other hand, it also has enormous potential for conflict. The potential for large conflict in Indonesia is not only due to the diversity of races and ethnicities but also because of many other differences in beliefs and culture. All of this is mixed into one in Indonesia. To avoid this conflict, a sense of tolerance is needed to maintain harmony between religious communities in Indonesia. One area that can maintain a sense of tolerance and harmony is Minahasa, North Sulawesi, where the majority Christian population can live side by side in harmony with Muslim minorities. Kampung Jawa Tondano (Jaton) is a village full of history with the majority of its residents being Muslim, but the villagers can exist, adapt and interact well with other Minahasa residents who are Christian.